A meta-analysis of risk factors for intimate partner homicide: examining male perpetration and female victimization - Spencer, Chelsea Marie (Kansas State University, 2018)
Intimate partner homicide (IPH) is a serious problem throughout the world. Research has identified a history of intimate partner violence (IPV) as a risk factor for IPH (Campbell et al., 2007). However, we know that not all individuals who perpetrate IPV end up perpetrating IPH, and not all victims of IPV end up becoming victims of IPH. There is a need to identify additional risk factors for IPH in order to potentially help identify individuals who may be at a greater risk for IPH perpetration or victimization. In this study, we conducted a meta-analysis on risk factors for male IPH perpetration and female IPH victimization. This meta-analysis examined results from 17 studies, which included 148 effect sizes to be used in the analysis. The overall sample size included in the study was 10,143. This study compared IPV samples and IPH samples as a means to aid in identifying risk factors that may place individuals who are victims or perpetrators of IPV at a greater risk for IPH perpetration or victimization. Results of our analyses indicated that the strongest risk factors for male IPH perpetration were the perpetrator having direct access to a gun, perpetrator’s previous threats with a weapon, perpetrator’s previous non-fatal strangulation, perpetrator’s previous rape of the victim, perpetrator’s demonstration of controlling behaviors, perpetrator’s previous threats to harm the victim, and the perpetrator’s previous stalking of the victim. We found that the strongest risk factors for female IPH victimization were the victim being abused by the perpetrator while pregnant, the victim’s substance abuse, the victim having less than a high school education, being separated from the perpetrator, and having children from a previous relationship (not with the perpetrator). Implications for law enforcement personnel, victim advocates, mental health professionals, as well as other professionals who may be in contact with potential IPH perpetrators and victims are discussed.
Keywords: Meta-analysis; Intimate partner homicide; Risk factors